Latent fingermark detection using functionalised silicon oxide nanoparticles: Investigation into novel application procedures. (June 2022) - Lee, Po Lun Timothy; Kanodarwala, Fehmida K.; Lennard, Chris; Spindler, Xanthe; Spikmans, Val; Roux, Claude; Moret, Sébastien
Abstract: Investigations into the application of carboxyl-functionalised silicon oxide nanoparticles doped with a ruthenium complex (RuBpy-doped CES-SiO2 NPs) for latent fingermark development on non-porous surfaces were reported in previous studies. These studies suggested that an optimised NP-based method demonstrated advantages in fingermark selectivity and sensitivity. To continue the series of research into using RuBpy-doped CES-SiO2 NPs for fingermark detection, the versatility and overall practicality of the optimised SiO2 NP-based reagent for latent fingermark detection and enhancement was evaluated. When the optimised NP-based method was used in a repeated fashion (application of multiple NP treatment cycles), it was found that the overall fingermark detection quality increased across the evaluated fingermarks without a high risk of overdevelopment. The possibility of incorporating the optimised NP-based reagent for potential operational use (e.g., at crime scenes) was successfully demonstrated via spray application on three test surfaces (aluminium foil, transparent polypropylene film and green polyethylene film). It was also shown that further enhancement of "spray-detected" fingermarks was achievable via subsequent treatment using the NP-based reagent in a colloidal dispersion bath. Additionally, the compatibility of the optimised NP-based method with two-step cyanoacrylate fuming for latent fingermark detection was evaluated. It was concluded that the two techniques are not compatible for application in a fingermark detection sequence. While encouraging results were demonstrated in this study, further optimisation and comparison will be required before the multiple-treatment and spray-treatment approaches can be considered for operational implementation. Highlights: Fingermark detection using optimised RuBpy-doped CES-SiO2 NPs was further improved. Investigations into overall practicality and versatility were completed. The NP-based method is not compatible for use in sequence with cyanoacrylate fuming. Multiple NP treatment cycles can be used for further fingermark enhancement. Fingermarks can be detected via spray application of the optimised NP-based reagent.